MODEL HUBUNGAN PARIWISATA, KINERJA PEREKONOMIAN DAN KEMISKINAN DI KABUPATEN BADUNG, BALI - Patera I Made; Suardana I Wayan (PIRAMIDA, 2015)
Tourism and poverty’s phenomenon had already been known since the birth of human civilization. In the 1980spoverty became a serious concern of practitioners and scholars in various part of the world, including Indonesia.Poverty is not only understood in understanding as an abstract concept, but also as a reality of economic injusticeand inability to meet basic human needs in some rich countries but also in many developing countries in theworld. The problem of poverty is a fundamental and tourism is one of the many ways to solve this. The objectiveof this paper is to study the role of tourism to poverty alleviation including: 1) to analyze the influence of tourismdevelopment toward economic performance; 2) to analyze the effect of economic performance on poverty eradication;3) to analyze the influence of tourism on poverty alleviation; 4) to formulate a strategy to increase tourism’s rolein poverty alleviation in Badung Regency. This study uses quantitative approach supported by secondary data andqualitative approach using primary data obtained through in-depth interviews and focus group discussions. Researchwas conducted in South Badung Regency in the most developed tourism growth and considered the richest districtamong all regencies in Bali Regencies. Various attempts have been made to alleviate poverty, however have notbeen able to resolve poverty problems.